Immunogenicity and safety of a multi-human dose formulation of Biological E’s 14-valent pneumococcal polysaccharide conjugate vaccine (PNEUBEVAX 14®) administered to 6–8-week-old healthy infants: a phase 3, single-blind, randomized, active-controlled study - Thuluva, Subhash; Matur, Ramesh V.; Gunneri, Subbareddy; Mogulla, Rammohan Reddy; Thammireddy, Kamal; Peta, Kalyan Kumar; Paliwal, Piyush; Mahantshetti, Niranjana S.; Banala, Ramesh Kumar; Siddaiah, Prashanth (Frontiers in Immunology, 2025)
BackgroundPneumococcal conjugate vaccines (PCVs) have considerably reduced the burden of invasive pneumococcal disease (PD) worldwide. Consequently, though, there has been an increase in non-vaccine serotype-induced PD particularly at both the extremes of age. Biological E has developed a 14-valent PCV (PNEUBEVAX 14®) that includes additional serotypes 22F and 33F. PNEUBEVAX 14® was shown to be safe, immunogenic, and non-inferior to Prevenar-13® (PCV-13) when administered to infants in a pivotal phase 3 trial. In this study, the multi-dose presentation of PNEUBEVAX 14® with 2-phenoxyethanol as a preservative was assessed for safety and immunogenicity in infants.MethodsThis was a phase 3, single-blind, randomized, active-controlled study in 6–8-week-old healthy infants, conducted at three sites across India. The safety and immunogenicity of multi-dose presentation of PNEUBEVAX 14® were assessed in a 6–10–14-week dosing schedule, with 300 infants randomized to receive either PNEUBEVAX 14® or PCV-13. Safety-wise solicited local reactions and systemic events, unsolicited adverse events (AEs), serious AEs, and medically attended AEs (MAAEs) were recorded and analyzed. Immunogenicity was assessed by measuring anti-pneumococcal capsular polysaccharide (anti-PnCPS) immunoglobulin G (IgG) antibodies for all 14 serotypes, as well as cross-reactivity to serotype 6A.FindingsThe safety aspects of the multi-dose presentation of PNEUBEVAX 14® and PCV-13 were comparable with 23.3% of subjects having AEs in each of the two arms. There were no serious AEs, medically attended AEs, or deaths in either of the two study arms. Reported AEs were mild and solicited in nature, with injection site swelling and injection site pain being the most common AEs in both arms. The multi-dose presentation of PNEUBEVAX 14® was found to induce a robust immune response, including the new serotypes 22F and 33F. Importantly, PNEUBEVAX 14® also induced cross-reactive antibodies against serotype 6A.InterpretationThe multi-dose presentation of PNEUBEVAX 14® is both safe and immunogenic when administered to 6–8-week-old infants in a 6–10–14-week dosing schedule. These results extend the findings of a pivotal phase 3 study of the single-dose presentation of PNEUBEVAX 14® that showed that it was safe, robustly immunogenic, and non-inferior to PCV-13 in the same age group and dosing schedule. Taken together, these data suggest that both the single-dose and multi-dose presentations of PNEUBEVAX 14® can be safely administered to infants to prevent pneumococcal disease caused by Streptococcus pneumoniae.Clinical Trial Registrationhttps://ctri.nic.in/Clinicaltrials/pmaindet2.php?EncHid=NTk0MzA=&Enc=&userName=, identifier CTRI/2021/10/037067.